The 16th National Information Day: Open Science, Open Data, Open Access, Bulgarian Open Science Cloud - Stanchev, Peter; Karaivanova, Aneta; Stancheva, Mikaela; I. Foteva, Elitsa; Iliev, Jordan; Paneva-Marinova, Desislava; Dobreva, Milena; Gandova, Teodora (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2025)
This paper gives a comprehensive overview of the current landscape and the ongoing efforts regarding open science at both national and international level, focusing on open access to scientific information, open data, and the Bulgarian Open Science Cloud.
Keywords: Open Access; Access to Knowledge; Open Science; Open Data; Repositories